ANALISIS KORELASI NILAI NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) DENGAN SUHU PERMUKAAN TANAH DI KHDTK UNIVERSITAS LAMBUNG MANGKURAT - Wilda Hatipah Yasmine; Ahmad Jauhari; Rina Muhayah Noor Pitri (Universitas Lambung Mangkurat, 2022)
This study means to examine the correlation of the Normalized Difference Vegetation Index (NDVI) with the land surface temperature at KHDTK of Lambung Mangkurat University using a combination of remote sensing, GIS, and field observations. The results showed that in the KHDTK area, the NDVI values ranged from 0.07 to 0.88. The estimation of land surface temperature based on the validation between the temperature of the image analysis results and the results of field observations ranged from 25.60°C to 31.90°C. The results of the geostatistical correlation analysis obtained the equation y = 35.5551 – 8.86213x with a coefficient of determination (R2) of 0,3623 and a correlation coefficient (r) of 0.6019. From this equation, it can be interpreted that NDVI and land surface temperature have a negative correlation or are inversely proportional to the level of a strong correlationPenelitian ini bertujuan menganalisis korelasi nilai Normalized Difference Vegetation Index (NDVI) dengan suhu permukaan tanah di KHDTK Universitas Lambung Mangkurat menggunakan teknik kombinasi antara penginderaan jauh, SIG dan observasi lapangan. Hasil penelitian menunjukkan pada area KHDTK nilai NDVI berkisar antara 0,07 sampai 0,88. Estimasi suhu permukaan tanah berdasarkan validasi antara suhu hasil analisis citra dengan hasil observasi lapangan berkisar antara 25,60°C sampai dengan 31,90°C. Hasil analisis korelasi geostatistik didapatkan persamaan y = 35,5551 – 8,86213x dengan nilai koefisien determinasi (R2) sebesar 0,3623 dan koefisien korelasi (r) sebesar 0,6019. Dari persamaan tersebut dapat diartikan antara NDVI dengan suhu permukaan tanah memiliki korelasi negatif atau berbanding terbalik dengan tingkat hubungan korelasi kuat